Pengembangan Media Pembelajaran “SKIAN” (Sejarah Kebudayaan Islam Animasi) Berbasis Aplikasi iSpring Suite pada Mata Pelajaran Sejarah Kebudayaan Islam Kelas X di SMA Madinatul Ulum - Fitri Khoirotun Nasyiroh; Hidayatur Rohmah (MASALIQ, 2025)
This study is motivated by the limited research on the development of interactive learning media for Sejarah Kebudayaan Islam (Islamic Cultural History, SKI), amidst the continued dominance of conventional methods that tend to be less engaging and the underutilization of Information and Communication Technology (ICT), which negatively affects students' learning interest and comprehension. The aim of this research is to develop an interactive learning media titled "SKIAN" (Sejarah Kebudayaan Islam Animasi), based on the iSpring Suite application, deemed suitable for Grade X SKI subjects at SMA Madinatul Ulum. The study employed a Research and Development (R&D) method using the ADDIE model, comprising analysis, design, development, implementation, and evaluation stages. The trial subjects included two media experts, one Islamic Education teacher as a content expert, and 20 Grade X students. Data were collected through observation, interviews, and questionnaires, and analyzed quantitatively. The results showed that the SKIAN media was rated highly feasible by media experts, with average scores of 94% and 84%, considered good by the content expert with a score of 71%, and received a positive response from students with a score of 71.1%. The media proved effective in increasing learning interest, supporting material comprehension, and creating a more interactive and engaging learning environment. The study concludes that SKIAN is a viable innovative alternative for SKI instruction. Its implications include theoretical contributions to the literature on ICT-based learning media and practical recommendations for teachers to integrate technology effectively, as well as suggestions for future researchers to enhance its features and evaluate its effectiveness in broader contexts.